Spectrophotometric Determination of Hexadecyltrimethylammonium Bromide with Chromeazurol S and Aluminum - Sha, Ou; Liao, Yin; Zhou, Yun; Ma, Weixing (Asian Journal of Chemistry, 2012)
A new spectrophotometric method was proposed for direct determination of hexadecyltrimethylammonium bromide in wastewater. The method is based on the formation of ternary complex, Al(III)-chromeazurol S (ACS)-hexadecyltrimethylammonium bromide. Under the optimum reaction conditions, hexadecyltrimethylammonium bromide reacts with Al(III) and chromeazurol S to form a ternary complex with maximum absorption peak at 635 nm. The absorbance and hexadecyltrimethylammonium bromide showed a good linear relationship with Bill laws in the 5-100 μg mL-1 concentration range, the correlation coefficient r = 0.9971, the recovery range is in 99.75-104.15 %. The proposed method based on the above colour reaction is simple and rapid. It has been applied to the determination of hexadecyltrimethylammonium bromide in water samples with satisfactory results.